Insights into foraging behavior from multi-day sound recording tags on goose-beaked whales (Ziphius cavirostris) in the Southern California Bight - Coates, Shannon N.; Sweeney, David A.; Falcone, Erin A.; Watwood, Stephanie L.; Rone, Brenda K.; DeRuiter, Stacy L.; Barlow, Jay; Dolan, Karin A.; Morrissey, Ronald P.; DiMarzio, Nancy A.; Jarvis, Susan M.; Andrews, Russel D.; et al. (Frontiers in Marine Science, 2024)
Goose-beaked whales (Ziphius cavirostris) are deep-diving cetaceans known for their elusive nature and specialized foraging behavior. In 2019 and 2020, six telemetry tags were deployed on these whales in Southern California, resulting in 395 h of acoustic and diving data. Foraging dives were manually identified by the presence of echolocation pulses and buzzes, and generalized additive models assessed factors influencing foraging behavior. The median bathymetric depth at foraging sites was 1,419 m (IQR = 359), and the maximum dive depth was highly correlated with bathymetry depth. Individuals started echolocating on descent at a median depth of 410 m (IQR = 74); pulses were not observed shallower than 292 m. Echolocation ceased during the bottom phase for 81.6% of dives, at a median depth of 1,265 m (IQR = 472); pulses were not observed shallower than 587 m on ascent. The median depth of buzzes was 1,215 m (IQR = 479) with 63% occurring during the bottom phase. Deeper dives correlated with longer durations of diving and echolocation, greater echolocation end depths, and wider bottom phase echolocation depth inter-quartile range. The median difference between dive depth and bottom phase median echolocation depth was 98.3 m (IQR = 48.5), suggesting whales in this region forage in a narrow band close to the seafloor. In the San Nicolas Basin, individuals exhibited longer echolocation durations, produced more pulses, and started and ended echolocating at greater depths compared to adjacent regions. These records validate and expand upon previous studies, providing insights into factors influencing foraging behavior in an area with high anthropogenic disturbance.